2014
DOI: 10.4194/1303-2712-v14_4_03
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, the larval development of freshwater angelfish, Pterophyllum scalare, was described under controlled aquarium conditions. Major histomorphological changes and the allometric growth patterns during the larval development have been described. The larvae were obtained from three pairs of freshwater angelfish, which were maintained in glass tanks. The larvae were sampled for measurement and photography. They were observed under a stereomicroscope, photographed using a photomicrographic system. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…In addition, since the micromanipulation process requires fast, precise manipulation techniques, the transgenic plasmid must be microinjected into the embryos at the correct stage of one cell. Angel sh embryos develop at a single-cell stage for approximately 20 minutes [25], which is enough time to transfer a large amount of plasmid to be made at one time into multiple egg embryos. In light of this, even though embryo survival after microinjection was poor in this study, the percentage of embryos expressing red uorescence protein expression was high (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, since the micromanipulation process requires fast, precise manipulation techniques, the transgenic plasmid must be microinjected into the embryos at the correct stage of one cell. Angel sh embryos develop at a single-cell stage for approximately 20 minutes [25], which is enough time to transfer a large amount of plasmid to be made at one time into multiple egg embryos. In light of this, even though embryo survival after microinjection was poor in this study, the percentage of embryos expressing red uorescence protein expression was high (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…After microinjection, the survival rate of angel sh eggs was only 2.3 percent, which is 60-80 percent lower than that of zebra sh eggs [26]. Angel sh are species that lay eggs on substrates and are particularly sensitive to changes in environmental circumstances [25,27]. As a result, embryo survival is poor because of egg harvest and the in uence of the micromanipulator on embryos during gene transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the larval development in common cichla (Cichlasoma dimerus), discus (Symphysodon discus), angelfish (Pterophyllum scalare), and midas cichlid (Amphilophus spp.) were completed in around 24-42 days (Meijide and Guerrero 2000;Çelik 2010;Çelik et al 2014;Kratochwil et al 2015), the study conducted by Karadal (2016) on four mbuna cichlid species, including rusty cichlid (Iodotropheus sprengerae), kenyi (Maylandia lombardoi), auratus (Melanochromis auratus) and demasoni (Pseudotropheus demasoni), reported that the larval stages lasted 19-21 days. However, there are several studies conducted on the larval development of armored and suckermouth catfish species.…”
Section: A B C D E Discussionmentioning
confidence: 99%
“…Sport is considered to be a useful activity in the physical and mental development of individuals due to its positive contribution to the continuation of health status, prevention of obesity and diseases that may develop due to sedentary life and to the person's social life. 1,2 Regular exercise has proven to be an effective method to prevent obesity 3 , cardiovascular diseases 1 , diabetes, breast 4 , colon, rectal 5 and prostate 6 cancers. 7 Physical activity is known to reduce depression 8 , lower blood pressure 9 , positively affect bone health 10 , improve symptoms in fibromyalgia patients 11 , and reduce the risk of dementia.…”
Section: Introducti̇onmentioning
confidence: 99%